Clinical Evaluation of Cement Thickness Around Pre- Fabricated vs. Costume-Fabricated Posts - Zsuzsanna, Bardocz Veres; Diana, Cerghizan (European Scientific Journal, ESJ, 2016)
Objectives: The purpose of this study was to evaluate the variation of cement thickness in different regions of the root in case of prefabricated and custom-fabricated posts. Material and methods: Totally twelve extracted human incisors and premolars with single tooth canals were distributed among 3 experimental groups of 4 specimens each. They were treated endodontically and restored with prefabricated fibre posts or custom-fabricated metallic posts, cemented with different adhesive cements. Each sample was immersed in 1% methylene blue solution and after 10 days the teeths were sectioned into horizontal slices,resulting in three slices for each specimen. The distances between the canal wall and the post perimeter were measured on images of each slice with digital caliper. Results: The costume-fabricated post groups (group 2,3) obtained statistically significant lower cement thicknesses,in particular in the apical third. The prefabricated post group (group 1) showed the highest cement thickness. Cement thickness was less for the specimens prepared using direct impression technique.